Waninggap Bekai sebagai media Pendampingan Pastoral terhadap kasus Perselingkuhan dalam Keluarga Kristen di Kabupaten Merauke - Meivy Silvana Mahardika Moningka (Mahesa Research Center, 2023)
The purpose of this writing is to analyze Waninggap Bekai as a medium for pastoral assistance to cases of infidelity that occurred in Christian families in Merauke Regency. This writing is motivated by the fact that there are many cases of infidelity caused by the presence of a third person. A case of infidelity committed by a wife to a husband who is still in a legal marriage status and is in a harmonious Christian family circle. Waninggap Bekai or compassion as a heritage value is used as a medium to provide solutions from a Marind cultural perspective in collaboration with six assistance functions that are expected to provide assistance and serve as a medium in resolving cases of infidelity. The writing method used is a qualitative writing method, with data collection techniques through observation and interviews. This writing will describe the factors that cause infidelity, the philosophical foundations of Sumai Meaan, Waninggap Bekai as pastoral accompaniment media, the functions of pastoral accompaniment, and the design of the pastoral accompaniment approach which includes the goals and objectives of the accompaniment. The purpose of writing this article is to understand the cultural value of Waninggap Bekai as a medium for pastoral assistance by looking at the local wisdom values of the Merauke people.